2017
DOI: 10.1016/j.jacc.2017.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Ranolazine After Incomplete Percutaneous Coronary Revascularization in Patients With Versus Without Diabetes Mellitus

Abstract: BACKGROUND Chronic angina is more common in diabetes mellitus (DM) patients with poor glucose control. Ranolazine both treats chronic angina and improves glucose control. OBJECTIVES This study sought to examine ranolazine’s antianginal effect in relation to glucose control. METHODS We performed a secondary analysis of RIVER-PCI, a clinical trial in which 2,604 patients with chronic angina and incomplete revascularization following percutaneous coronary intervention (PCI) were randomized to ranolazine versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
15
0
1
Order By: Relevance
“…As primary efficacy outcome, change in A1C level from baseline was reported in 6 studies. [14][15][16][17]28,29 Compared with the placebo group, the combined results indicated that ranolazine significantly reduced the A1C level in patients with diabetes (WMD = −0.49%; 95% CI = −0.58 to −0.40; P < 0.00001; I 2 = 0%). In the subgroup analysis, the 2 predefined characteristics for stratifying the included studies had the same grouped result.…”
Section: Efficacy Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…As primary efficacy outcome, change in A1C level from baseline was reported in 6 studies. [14][15][16][17]28,29 Compared with the placebo group, the combined results indicated that ranolazine significantly reduced the A1C level in patients with diabetes (WMD = −0.49%; 95% CI = −0.58 to −0.40; P < 0.00001; I 2 = 0%). In the subgroup analysis, the 2 predefined characteristics for stratifying the included studies had the same grouped result.…”
Section: Efficacy Outcomesmentioning
confidence: 95%
“…However, selection bias was unclear in 3 trials, 16,17,29 and detection bias was classified as unclear in 2 trials 17,29 because of absence of detailed information. Overall, 1 trial 29 had a high risk of bias, 4 trials 14,15,28,30 had a low risk of bias, and the others 16,17 had an unclear risk of bias. No clinically significant cardiovascular events, including myocardial infarction, acute coronary syndrome, recent revascularization (including coronary artery bypass graft procedures or percutaneous coronary intervention), transient ischemic attack, or ischemic stroke ≤3 months prior to screening.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Interestingly, R reduced the incidence of new fasting glucose >110 mg/dl in patients without T2DM at baseline compared to placebo (31.8% versus 41.2%; p = 0.003). In a secondary analysis of RIVER-PCI trial, Faranoff et al [22] reported the efficacy of R in lowering HbA1c especially in patients with poor glucose control and that this efficacy was greater at 6 months than at 12 months.…”
Section: Glycometabolic Effect Of Ranolazine In Diabetic Patients Witmentioning
confidence: 99%
“…По данным субанализа этого исследования, у пациентов с сахарным диабетом (n = 961) ранолазин снижал уровень гемоглоби-на А1с, но не уменьшал тяжесть стенокардии через 12 мес. терапии [29]. Ранее X. Xu et al применяли триметазидин после ЧКВ у больных с сочетанием многососудистой ИБС и сахарного диабета [30].…”
Section: ишемическая болезнь сердцаunclassified